Respuesta :

Answer:

(a) [tex]x(x+2)[/tex]  (b) [tex]2x(x-3)[/tex]  (c) [tex]5x(3-2x^2)[/tex]  (d) [tex]3x^2(3+x)[/tex]

Step-by-step explanation:

For each expression, we need to factor out the GCF(Greatest common factor)

a)   [tex]x^2+2x[/tex]

Here, the GCF is  [tex]x[/tex]. So, we will get.....

[tex]x^2+2x\\ \\ =x(\frac{x^2}{x}+ \frac{2x}{x}) \\ \\ =x(x+2)[/tex]

b)   [tex]2x^2-6x[/tex]

Here, the GCF is  [tex]2x[/tex]. So, we will get......

[tex]2x^2-6x\\ \\ =2x(\frac{2x^2}{2x}- \frac{6x}{2x}) \\ \\ =2x(x-3)[/tex]

c)   [tex]15x-10x^3[/tex]

Here, the GCF is  [tex]5x[/tex]. So, we will get.......

[tex]15x-10x^3\\ \\ =5x(\frac{15x}{5x}- \frac{10x^3}{5x}) \\ \\ =5x(3-2x^2)[/tex]

d)   [tex]9x^2+3x^3[/tex]

Here, the GCF is  [tex]3x^2[/tex]. So, we will get.......

[tex]9x^2+3x^3\\ \\ =3x^2(\frac{9x^2}{3x^2}+ \frac{3x^3}{3x^2}) \\ \\ =3x^2(3+x)[/tex]

ACCESS MORE